Kualitas Air Sumur Berdasarkan Pemeriksaan Mikrobiologis di Pasar Tradisional - Amyati Amyati; Nor Wijayanti (Faletehan Health Journal, 2022)
Beringharjo traditional market has many visitors and traders who utilize the sanitation facilities. It requires the provision of clean water both in quality and quantity. Based on the results of interviews with traders, employees and visitors, they complained about the condition of the water which is yellow, cloudy, smelly and not tasty when cooked for consumption purposes. The purpose of this study was to test the clean water with microbiological parameters. The research was descriptive and used cross-sectional approach. The research population numbered 55 and the sample was determined by using purposive sampling technique. The sample amounted to 10 clean water. The variables of this study were Total coliform and E. coli in clean water. The data were analyzed by using MPN (most probable number) method. The results of the microbiological parameter test showed that 7 samples were positive contained coliform and E. coli which exceeded the quality standard. The test results from 10 samples of clean water found that 7 samples of water did not meet the clean water requirements because they exceeded the threshold value and 3 samples were in accordance with the requirements of sanitation hygiene.